Reshaping urban lives: design as social intervention towards community networks - Franqueira, Teresa (2007)
This paper aims to show some cases of creative communities based on collaborative services as a way to promote sustainable development. This scenario (creative communities and their services) offers design a different approach and a new opportunity to develop and enhance a sustainable future. The transition from the industrial age to the age of knowledge brings about diverse changes in the way we live. The collapse of the Welfare state and the globalisation have created new problems and, thus, new needs (Beck, 1999; Giddens, 1999; McLaughlin and Davidson, 1990). The urgency in finding new solutions to the problems arisen by this new world is bolstering a phenomenon of rebirth of the idea of alternative or intentional communities (McLaughlin & Davidson, 1985), that can be defined as “user-driven communities of innovation” or “creative communities”. These communities have at their core the participation and the democratisation of innovation, meaning that innovation in products or services is no longer the remit of established organizations (Leadbeater , 2006). These changes give us an opportunity to reinforce these type of behaviours through the design discipline. The role of design and designers is changing. As users get involved with designers in the creation of products and services (Leadbeater , 2006), new territories for the discipline are opened. It is possible that from now on design will be a co-participatory activity in which users become part of the entire project, not only as references or recipients but as real resources that shape the all project. Throughout this paper we will envisage to highlight the potential of collaboration between design and creative communities as a way to create social cohesion, environmental sustainable development and reinforcement of local economies. In order to do so, a number of cases that are being developed in some European cities will be presented. The structural differences between them will be demonstrated. These differences arising mainly from the fact that some of them are top-down initiatives with the direct participation of design; and others are bottom-up, more spontaneous, un-designed ones. In this framework design should act as an interface between these two levels, for top-down initiatives are strategic whilst bottom-up ones are more tactical or operative. If Design has the capacity of being both strategic and tactical, this means that it can potentiate people’s and government’s visions, creating scenarios according to those same visions. Design is about culture and creativity, is about problem solving, and these projects are solving problems arisen from everyday activities that people have to carry out in this complex society. Ultimately we aim to show that design as a strategic and tactical element is, alongside other disciplines, a critical element in the promotion, implementation and dissemination of these cases and its best-practices. The contents of this paper are part of an on-going research at the Research Unit DIS – Design and Innovation for Sustainability - of the Politecnico di Milano.